The Impact of Physical Chaos on the Visual Pollution of Architectural Form - Sham Mustafa Qadir (Sulaimani Journal for Engineering Sciences, 2017)
The visual pollution is one of the biggest problems of this era, and due to the increasing occurrence of visual pollution in the city of Sulaimaniya, made it necessary to do this research, where the research is trying to bridge the lack of winning the mechanism of the effect of chaos knowledge in the events of visual pollution in architectural form in the city of Sulaymaniyah. Achieving the goal of the study into the possibility of finding a mechanism that affect the chaos in the events of visual pollution in architectural form is in two steps, the first step to identify the architectural form’s terms, right down to the limits of practical study, and the second step by definition process to study in terms of the approved method, where dealing with practical study topic phases main, first clarify the extent of existence of visual pollution in architectural form, and then demonstrate the impact of the chaos on the formation of pollution, include hypotheses tested by identifying the methods used in the measurement and analysis methods, and between the theoretical side the need to rely on engineering methods (engineering visual graphic analysis) and the statistical study of architectural models at different levels, right down to the results of these analyzes discussed with the verification of hypotheses, and thus put conclusions. Research has found that chaos is one of the main reasons in the formation of visual pollution in architectural form in the city of Sulaimaniya, by affect in a negative way to cause visual pollution in architectural form influential on visual perception and mental state of the recipients, through a variety of mechanisms that appear disparity between the effect of each one of them , depending on the method employed.